REMIMAZOLAM VS. PROPOFOL IN SEDATION FOR OUTPATIENT PROCEDURES: SAFETY AND RAPID RECOVERY - Pedro do Valle Varela, João; Laura Maruschi, Ana; Polonine Poltronieri Jeronimo, Mikaella; Marques Cândido Pales, Lisiane; Lima Beninato, Rayan; Figueiredo Porto, Ricardo; Sayuri Louvain de Azevedo, Karen; Silva de Santana, Ícaro; Almeida Lima, Adeânio; Benício De Almeida Rochedo, Aline; Paula Pereira Maltez, Ana; da Silva Oliveira, Alvarino; et al. (Health and Society, 2025)
Sedation in outpatient procedures requires agents with a favorable pharmacokinetic profile, cardiovascular safety, and rapid recovery. Propofol, traditionally used, is effective but can cause hypotension and respiratory depression. Remimazolam, an ultra-short-acting benzodiazepine, emerges as a promising alternative, combining controllable sedation with an improved safety profile. This study aimed to compare the efficacy, safety, and recovery time of remimazolam versus propofol in patients undergoing outpatient procedures, to assess its clinical feasibility as a substitute or complement to propofol. This is a literature review with a qualitative and exploratory approach. The selection of studies was performed by consulting the PubMed, SciELO, ScienceDirect, and Scopus databases, considering full articles published in peer-reviewed scientific journals that analyze aspects related to the use of remimazolam and propofol in outpatient procedures. The time frame considered publications between 2020 and 2023, based on the oldest articles (da Silva, 2020; Melo, 2020; Rodrigues et al., 2020) and the most recent (Gomes et al., 2023; Carvalho et al., 2023). The data analyzed showed that remimazolam has sedative efficacy comparable to propofol, but with a lower incidence of hypotension, bradycardia, and respiratory depression. In addition, it showed greater predictability in recovery, especially in the elderly and patients with comorbidities. The time to cognitive function recovery and hospital discharge was similar between groups, with a slight advantage for remimazolam in some studies. Its reversibility with flumazenil also offers an additional margin of safety. It is concluded that remimazolam is a safe and effective alternative to propofol for sedation in outpatient procedures, with advantages in specific risk profiles. Despite its higher costs, its use may be preferred in vulnerable populations or in protocols that require rapid recovery and less hemodynamic instability.